Gut microbiome-mediated metabolism effects on immunity in rural and urban African populations - Martin Stražar (Nature Portfolio, 2021)
The authors profile stool metagenomics and plasma metabolomics in Tanzanian individuals and uncover a gradient of gut microbial profiles, from rural through urban Tanzania towards Western populations. Integration with ex vivo blood microbial stimulations reveals immune responses associated with histidine and arginine pathways, mediated by Bifidobacterium longum and Akkermansia muciniphila.